Site Diversity Gain Estimated from Rain Rate Records - Fiser, Ondrej (Radioengineering Society, 2003)
The site diversity is used to mitigate the rain attenuation on satellite links. The attenuation is estimated through the rain rate-rain attenuation conversion based on the Assis-Einloft physical model in this study. Through the comparison of instantaneous attenuations at two receiving sites the site diversity gain is estimated. Examples of rain rate measurements in the Czech Republic followed by the site diversity gain estimation are added. This gain is greater on west-east situation of receiving sites achieving 10 dB on 0.01% exceedance level/100 km.
Keywords: Site diversity; rain attenuation; satellite links; micro-wave communication